(untitled) (Indonesian Art and Justice Review, 2024)
In recent years, Indonesian artists have increasingly used their work as a tool for activism, tackling social, political, and environmental issues. This paper examines the role of art in Indonesian social justice movements, focusing on how contemporary artists address issues such as human rights, environmental degradation, gender inequality, and political repression. By analyzing key works from artivists—artists who combine activism with art—the paper explores how art becomes a medium for resistance, protest, and advocacy. It also considers the challenges artists face in navigating Indonesia’s complex political landscape and the role of art in pushing for social change in the context of censorship, state control, and public opinion.